Snapin-regulated late endosomal transport is critical for efficient autophagy-lysosomal function in neurons - Cai, Qian (2010)
Neuron maintenance and survival require late endocytic transport from distal processes to the soma where lysosomes are predominantly localized. Here, we report a role for Snapin in attaching dynein to late endosomes through its intermediate chain (DIC). Snapin (−/−) neurons exhibit aberrant accumulation of immature lysosomes, clustering and impaired retrograde transport of late endosomes along processes, reduced lysosomal proteolysis due to impaired delivery of internalized proteins and hydrolase precursors from late endosomes to lysosomes, and impaired clearance of autolysosomes, combined with reduced neuron viability and neurodegeneration. The phenotypes are rescued by expressing the snapin transgene, but not the DIC-binding defective Snapin-L99K mutant. Snapin overexpression in wild-type neurons enhances late endocytic transport and lysosomal function, while expressing the mutant defective in Snapin-DIC coupling shows a dominant-negative effect. Altogether, our study highlights new mechanistic insights into how Snapin-DIC coordinates retrograde transport and late endosomal-lysosomal trafficking critical for autophagy-lysosomal function, thus neuronal homeostasis.